Сontent of interferon-γ and interleukin-4 in blood serum of patients with chronic hepatitis С with mixed crioglobulinemia - O. P. Mashko; E. V. Ryabokon; A. V. Abramov (Zaporozhye State Medical University, 2012)
The examination of 82 patients with chronic hepatitis C showed that disbalance in the system of cytokines in patients with chronic hepatitis C with mixed cryoglobulinemia is most pronounced and characterized by the lowest content of interferon-γ and the highest content of interleukin-4 in blood serum. The disbalance in the cytokine system plays an important role in the development of signs of mixed cryoglobulinemia.